Inhibition rather than Enhancement of Hemostatic System Activation during Initiation of Oral Anticoagulant Treatment - Kyrle, Paul A; Brockmeier, Johannes; Weltermann, Ansgar; Eichinger, Sabine; Speiser, Wolfgang; Lechner, Klaus; Eichler, Hans-Georg (Thrombosis and Haemostasis, 1997)
Coumarin-induced skin necrosis is believed to be due to a transient hypercoagulable state resulting from a more rapid decline of the protein C activity relative to that of coagulation factors (F) II, IX and X during initiation of oral anticoagulant therapy. We studied hemostatic system activation during early oral anticoagulant treatment with a technique that investigates coagulation activation in the microcirculation.We determined in 10 healthy volunteers the concentrations of prothrombin fragment F1+2 (f1.2) and thrombin-antithrombin complex (TAT) in blood emerging from an injury of the microvasculature (bleeding time incision) before and after initiation of both high-inten- sity and low-intensity coumarin therapy. In addition, f1.2, TAT, activated F VII (F Vila) and the activities of FII, F VII, F X and protein C were measured in venous blood.A rapid decline of F VII and protein C was observed in venous blood with activities at 24 h of 7 ± 1% and 43 ± 2%, respectively, during the high-intensity regimen. A 20 to 30% reduction of f1.2 and TAT was seen in venous blood at 72 h with no major difference between the high- and the low-intensity regimen. F Vila levels were substantially affected by anticoagulation with a >90% reduction at 48 h during the high-intensity regimen. Following high-intensity coumarin, a >50% decrease in the fl.2 and TAT levels was found in shed blood at 48 h suggesting substantial inhibition of thrombin generation during early oral anticoagulation. An increase in the f1.2 and TAT levels was seen neither in shed blood nor in venous blood.Our data do not support the concept of a transient imbalance between generation and inhibition of thrombin as the underlying pathomechanism of coumarin-induced skin nekrosis.